2021
DOI: 10.1177/0739456x211002910
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Long-Term Housing Recovery after Technological Disaster Using a Virtual Audit with Repeated Photography

Abstract: Many communities face risks of technological disasters at fertilizer plants and other facilities. Understanding damage and rebuilding of housing supports planners in implementing policies that will enable recovery. Using repeat photography, this study audited housing rebuilding in West, Texas for three years following an explosion. Photos were combined with appraisal data to understand variation in rebuilding across parcels. Results indicate that rebuilding slows dramatically after year 1, leaving many parcels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 92 publications
(140 reference statements)
0
1
0
Order By: Relevance
“…In another study, Gomez-Cunya et al (2022) confirmed that sociodemographic characteristics of a community significantly affect the way they respond to disasters and recover. Hendricks and Meyer (2021) study long-term housing recovery by combining the repeat photography with appraisal data to identify the variation in reconstruction in Texas after disaster. Alisjahbana and Kiremidjian (2021) proposed a stochastic queuing approach for simulating the recovery after Lombok earthquake.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Gomez-Cunya et al (2022) confirmed that sociodemographic characteristics of a community significantly affect the way they respond to disasters and recover. Hendricks and Meyer (2021) study long-term housing recovery by combining the repeat photography with appraisal data to identify the variation in reconstruction in Texas after disaster. Alisjahbana and Kiremidjian (2021) proposed a stochastic queuing approach for simulating the recovery after Lombok earthquake.…”
Section: Introductionmentioning
confidence: 99%